Further Investigation of the Dimensionality of the Questionnaire for Eudaimonic Well-Being - Cromhout, Amanda; Schutte, Lusilda; Wissing, Marié P.; Schutte, Willem D. (Frontiers in Psychology, 2022)
The unidimensionality of the Questionnaire for Eudaimonic Well-being (QEWB) was proposed and supported in the original scale development study, but a subsequent study questioned the analytical method used and found support for a three- and four-factor structure instead. This study explored the one-, three-, and four-factor structure and measurement invariance of the QEWB in four nonprobability South African samples using confirmatory factor analysis (CFA), bifactor CFA, exploratory structural equation modelling (ESEM), and bifactor ESEM. Three student samples completed the English (n = 326, Sample 1), Afrikaans (n = 478, Sample 2), or Setswana (n = 260, Sample 3) version of the QEWB. An adult sample (n = 262, Sample 4) completed the English version. The one-factor structure revealed poor fit for student Samples 1-3. Although the four-factor models generally showed slightly better fit than the three-factor models, the latter was preferred for parsimony. The bifactor ESEM model displayed good fit for Samples 1-3 with the general factor and some specific factors attaining sufficient reliability scores, pointing to the potential use of the scale in these samples. Configural invariance between the student samples was supported. For Sample 4, none of the models displayed good fit and the use of the QEWB in this sample is therefore not recommended. The results point towards the existence of a global eudaimonic well-being factor and the interrelatedness of facets of eudaimonic well-being. The influence of developmental phase on the manifestation and measurement of eudaimonic well-being should be explored in future.